An In Vitro Microfluidic Alveolus Model to Study Lung Biomechanics - Kumar, Vardhman; Madhurakkat Perikamana, Sajeesh Kumar; Tata, Aleksandra; Hoque, Jiaul; Gilpin, Anna; Tata, Purushothama Rao; Varghese, Shyni (Frontiers in Bioengineering and Biotechnology, 2022)
The gas exchange units of the lung, alveoli, are mechanically active and undergo cyclic deformation during breathing. The epithelial cells that line the alveoli contribute to lung function by reducing surface tension via surfactant secretion which is highly influenced by the breathing associated mechanical cues. These spatially heterogenous mechanical cues have been linked to several physiological and pathophysiological states. Here, we describe the development of a microfluidically-assisted lung cell culture model that incorporates heterogeneous cyclic stretching to mimic alveolar respiratory motions. Employing this device, we have examined the effect of respiratory biomechanics (associated with breathing-like movements) and strain heterogeneity on alveolar epithelial cell functions. Furthermore, we have assessed the potential application of this platform to model altered matrix compliance associated with lung pathogenesis and ventilator induced lung injury. Lung microphysiological platforms incorporating human cells and dynamic biomechanics could serve as an important tool to delineate the role of alveolar micromechanics on physiological and pathological outcomes in the lung.